The Mediating Role of Brand Image in the Effect of Attitudes Toward Activist Advertising on Customer Loyalty - Kuldaş, Erkut (International Review of Management and Marketing, 2026)
This study examines the mediating role of brand image in the effect of attitudes toward activist advertising on customer loyalty. As brands increasingly take stances on social and political issues, understanding how consumers respond to activist messages has become critical for marketing strategy. Data were collected from 409 participants residing in Turkey through an online survey and analyzed using Jamovi software. Confirmatory factor analysis (CFA) was conducted to assess the validity and reliability of the measurement scales, followed by path analysis and bootstrap-based mediation analysis. The findings reveal that advertising value and entertainment directly affect customer loyalty, while the effects of informativeness, deceptiveness, and irritation on loyalty operate indirectly through brand image. Notably, deceptiveness positively affects brand image—a finding that, contrary to the prevailing literature, may reflect how young and educated consumers interpret provocative activist messages. Brand image has a strong positive effect on customer loyalty. Mediation analysis shows that brand image significantly mediates the effects of advertising value, informativeness, deceptiveness, and entertainment on customer loyalty, while irritation has no significant mediation effect. By integrating multiple attitude dimensions within a single mediation framework, this study provides theoretical contributions to the brand activism literature and offers practical implications for marketing managers in designing effective activist advertising strategies.